STRATEGY FOR THE INDUSTRIALIZATION OF DAIRY CATTLE BREEDING IN DEVELOPING COUNTRIES - Bekzod, Djurayev; Chori , Kulmatov; Shukhrat, Nematjanov (Journal of Medical Genetics and Clinical Biology, 2024)
The industrialization of livestock products, including dairy farming, is one of the important issues in the context of population growth and global climate change. Also, a number of problems, such as meeting the population's demand for quality food and ensuring food safety, require the application of scientific achievements to the sector and increase investment attractiveness. Milk production in our republic poses a difficult question of introducing industrial technologies to animal husbandry while fully meeting the demands of the domestic market. If we take into account that 85% of the milk produced in our republic is produced by farmers' farms, we can understand that the intensification of the dairy sector is significantly complicated. At the same time, it is possible to reduce the cost of products and rational use of resources by improving the activity of livestock farmers.